2016
DOI: 10.1016/j.jaci.2016.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing identifies micro-RNA–based biomarker panel for Kawasaki disease

Abstract: Capsule Summary 22Diagnosing Kawasaki disease (KD) currently relies on physicians' experience, 23 making it difficult to accurately diagnose KD. Using NGS, qPCR and machine 24 learning algorithm, we identified a miRNA-based biomarker panel with high 25 accuracy. 26 27 Kawasaki disease (KD) is an autoimmune disease preferentially attacking 32 children younger than five years old. Symptoms of KD include fever for at least 33 five days, oral mucosal inflammation, non-supportive conjunctivitis, 34 lymphadenopathy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 10 publications
3
47
0
Order By: Relevance
“…Support vector machine (SVM, lib-SVM version 3.22) is a type of machine learning algorithm and is good in dealing with binary classification problem, applied in many biomedical studies [23,28,29]. In this study, we applied the lib-svm module to derive a classification model.…”
Section: Machine Learning Jobmentioning
confidence: 99%
See 2 more Smart Citations
“…Support vector machine (SVM, lib-SVM version 3.22) is a type of machine learning algorithm and is good in dealing with binary classification problem, applied in many biomedical studies [23,28,29]. In this study, we applied the lib-svm module to derive a classification model.…”
Section: Machine Learning Jobmentioning
confidence: 99%
“…As a kind of machine learning algorithm, SVM is usually applied to handle biomedical problems to discriminate treatment from control or disease from normal [28,29]. We have also applied SVM to develop a classification model that discriminates febrile controls from KD subjects [23,24]. Since we have identified cg23677000, cg0408544, and hepcidin as potential biomarkers, we used the methylation percentages of cg23677000 and cg04085447, as well as the plasma ELISA level of hepcidin, as SVM vectors for each subject.…”
Section: The Performance Of the Support Vector Machines (Svm) Classifmentioning
confidence: 99%
See 1 more Smart Citation
“…A senior clinician diagnosed patients with KD in accordance with the recommended universal KD criteria published by the American Heart Association (AHA) [27]. The diagnostic criteria of KD includes fever that lasts longer than ve days, as well as four of the following ve symptoms: diffuse mucosal in ammation with strawberry tongue and ssure lips, bilateral non-purulent conjunctivitis, indurative angioedema of the hands and feet, dysmorphic skin rashes, and unilateral cervical lymphadenopathy, as stated in our previous reports [28]. Once their symptoms were remitted, KD patients were administered a developmental or cognitive assessment in either outpatient department or in the ward.…”
Section: Participantsmentioning
confidence: 95%
“…More than 25 miRNAs have been identified for differentiating patients with KD from patients with fever using next‐generation sequencing. Quantitative polymerase chain reaction was selected for further analysis of some of these miRNAs, but researchers did not find a connection between miRNA‐149 and KD . In searching the literature, we found that miRNA‐149 has a definite association with some cancers, such as lung cancer, colorectal cancer, laryngeal squamous cell carcinoma, hepatocellular carcinoma, and neuroblastoma .…”
Section: Introductionmentioning
confidence: 99%